1995
DOI: 10.1063/1.469143
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the NH+NO reaction

Abstract: A threedimensional quantum mechanical study of the NH+NO reactionsWe present a quasiclassical trajectory study of the NHϩNO reaction using a global potential energy surface that is capable of describing branching to the HϩN 2 O and OHϩN 2 products after initial formation of a HNNO intermediate complex. The surface is based on a many-body expansion wherein fragment potentials for the species N 2 H, HNO, and N 2 O are incorporated, using either previously developed potentials, or in the case of N 2 O, a newly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 29 publications
5
42
1
Order By: Relevance
“…As discussed in the text, the isomerization barrier between HNNO and NNOH would need to be significantly lower to have N2 + OH dominate at lower temperature. Bradley et al (1995), who report a branching fraction of 13 ± 3% for the N2 + OH channel and show that decreasing the isomerization barrier by 40 kllmol increases the branching fraction by less than a factor of two. An additional feature of interest in Fig.…”
Section: ---mentioning
confidence: 95%
“…As discussed in the text, the isomerization barrier between HNNO and NNOH would need to be significantly lower to have N2 + OH dominate at lower temperature. Bradley et al (1995), who report a branching fraction of 13 ± 3% for the N2 + OH channel and show that decreasing the isomerization barrier by 40 kllmol increases the branching fraction by less than a factor of two. An additional feature of interest in Fig.…”
Section: ---mentioning
confidence: 95%
“…Theoretical studies of the thermal deNO x process [21][22][23][24][25][26][27][28] suggest the reaction of NH 2 with NO to be a primary product channel leading to N 2 and H 2 O, where NH 2 NO has been considered to be a crucial intermediate. The secondary products from this channel seem to be N 2 H + OH, 21,23,24,28 which act as the chain-branching step allowing the process to proceed.…”
Section: Introductionmentioning
confidence: 99%
“…This was the original goal of the present study. The buildup time of р100 fs is shorter than the 600 fs HNNO † lifetime calcu-lated by Bradley et al 6 who used the method of classical trajectories. This suggests that the cluster reaction does not go through the HNNO † intermediate but proceeds via direct attack at the oxygen.…”
Section: Discussionmentioning
confidence: 85%
“…The large amount of N 2 vibrational excitation reported by Böhmer et al could not be reproduced by the study of Bradley et al, 6 who calculated trajectories and found considerably less N 2 vibrational excitation for reactions that proceed via the HNNO † intermediate. This discrepancy remains unexplained.…”
Section: Introductionmentioning
confidence: 88%